Experiences with Unerupted Anterior and Posterior Teeth - Goh Gek Kiow; Kaan Sheung K. (Sciendo, 1993)
The causes of tooth impaction are as numerous as are ways to manage the problem. Treatment is usually instituted only after an unfavourable eruption prognosis of the impacted tooth has been established from radiographic and clinical examination. Advantages of guided eruption and surgical removal have to be weighed. Fifteen cases of various degrees of impaction, difficulty of treatment, complications and failures of eruption are discussed.